Proposed Parallel Algorithms to Encryption Image Based on Hybrid Enhancement RC5 and RSA - Hussein, Khaled Ali; Kareem, Taha Basil (2019 International Engineering Conference (IEC), 2019)
In recent years, image encryption algorithms have expanded for the defense of information from attackers to provide privacy to recipients. RC5 is a well-known block cipher which has some disadvantages such as weak against differential attacks and can be used for image encryption. RSA is an asymmetric key algorithm to provide privacy to carry information across the network which has some disadvantages such as require a greater amount of calculation that leads to the increased time. In this paper, the proposed system based on the use of the parallel environment in two proposed enhancement algorithms (ERC5 and ERSA) to get fast as possible with efficient encryption and decryption for the images. Enhancement RC5 algorithm (ERC5) that use for encrypts image by using four different cipher keys and four cores, instead of using a single key and one core. Enhancement RSA algorithm (ERSA) that use for encrypts keys ERC5 by using four prime numbers, two public keys, two private keys, and four cores, rather than using two prime numbers, one public key, one private key, and one core. According to the results of security analysis, the speed of the proposed system based on parallel environment is greater than the original (RC5, RSA) algorithms based a sequential environment, Increased the time to knowledge the private keys and effectively determine it, which makes the proposed system stronger against brute force attacks, the differential and statistical attacks.